2016
DOI: 10.15252/msb.20156608
|View full text |Cite
|
Sign up to set email alerts
|

Translation elicits a growth rate‐dependent, genome‐wide, differential protein production in Bacillus subtilis

Abstract: Complex regulatory programs control cell adaptation to environmental changes by setting condition‐specific proteomes. In balanced growth, bacterial protein abundances depend on the dilution rate, transcript abundances and transcript‐specific translation efficiencies. We revisited the current theory claiming the invariance of bacterial translation efficiency. By integrating genome‐wide transcriptome datasets and datasets from a library of synthetic gfp‐reporter fusions, we demonstrated that translation efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 47 publications
(114 reference statements)
5
68
0
Order By: Relevance
“…Such an inverse correlation was also reported in various other studies, for example on the production of a nuclease with E. coli (Cheng et al, ), a β‐aminopeptidase with E. coli (Heyland, Blank, & Schmid, ), GFP with B. subtilis (Borkowski et al, ), GFP with E. coli (Bienick et al, ), or LacZ with E. coli (Klumpp, Zhang, & Hwa, ). In these studies, the observed YP/X0.25em=0.25emftrue(µtrue) relations were explained by the redirection of metabolic flux to meet the increased energy demand from heterologous protein production (Heyland et al, ) and modeling of growth‐rate‐dependent ribosomal capacity (Bienick et al, ; Borkowski et al, ; Klumpp et al, ). However, these reports concerned intracellular protein production in batch cultivations, meaning that the observed reduced growth rates were a result of heterologous protein biosynthesis.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…Such an inverse correlation was also reported in various other studies, for example on the production of a nuclease with E. coli (Cheng et al, ), a β‐aminopeptidase with E. coli (Heyland, Blank, & Schmid, ), GFP with B. subtilis (Borkowski et al, ), GFP with E. coli (Bienick et al, ), or LacZ with E. coli (Klumpp, Zhang, & Hwa, ). In these studies, the observed YP/X0.25em=0.25emftrue(µtrue) relations were explained by the redirection of metabolic flux to meet the increased energy demand from heterologous protein production (Heyland et al, ) and modeling of growth‐rate‐dependent ribosomal capacity (Bienick et al, ; Borkowski et al, ; Klumpp et al, ). However, these reports concerned intracellular protein production in batch cultivations, meaning that the observed reduced growth rates were a result of heterologous protein biosynthesis.…”
Section: Resultssupporting
confidence: 75%
“…Such an inverse correlation was also reported in various other studies, for example on the production of a nuclease with E. coli (Cheng et al, 2003), a β-aminopeptidase with E. coli (Heyland, Blank, & Schmid, 2011), GFP with B. subtilis (Borkowski et al, 2016), GFP with E. coli (Bienick et al, 2014), or LacZ with E. coli (Klumpp, Zhang, & Hwa, 2009). In these studies, the observed…”
Section: Data Processingsupporting
confidence: 81%
See 1 more Smart Citation
“…Normalizing to the genome-wide average should help to mitigate this effect. Second, research has shown that at higher growth rates, ribosomal protein genes make up an increasingly larger fraction of bacterial proteomes (Borkowski et al 2016). Thus, relative differences in S between ribosomal protein coding genes and the genome as a whole should reflect the selective pressure for increased ribosomal protein production during periods of rapid growth.…”
Section: Resultsmentioning
confidence: 99%
“…3A). The use of resources for the synthesis of ribosomal proteins typically reflects the growth rate of the bacteria (Bremer and Dennis 1996;Borkowski et al 2016). Indeed, we observe a precise linear correlation between the growth rate of the strains and the fraction of ribosomal proteins (Fig.…”
Section: The Gene Expression/translation Machinerymentioning
confidence: 99%